Mortality Among Hardmetal Production Workers: The Swedish Cohort. Issue 12 (December 2017) - Westberg, Håkan; Bryngelsson, Ing-Liss; Marsh, Gary; Buchanich, Jeanine; Zimmerman, Sarah; Kennedy, Kathleen; Esmen, Nurtan; Svartengren, Magnus
Abstract : Background: The mortality pattern was determined in a cohort of 16, 999 white and blue-collar workers in the Swedish hardmetal industry, particularly for cobalt exposure and lung cancer. Methods: The mortality follow-up analysis in the Swedish Mortality register covered the period from 1952 to 2012. The exposure measures were ever/never exposed, duration of exposure, cumulative, and mean cobalt concentrations. Results: The mortality of all causes was significantly increased, highly associated with the short-term employed workers. A negative exposure–response was found for lung cancer and duration of exposure. An exposure–response was determined for cumulative and mean cobalt exposures analyzed by quartiles, but not for exposure classes. Internal comparison analysis using proportional hazard showed no exposure–response. Conclusions: The cohort lung cancer mortality showed no correlation to cobalt, nickel, or tungsten exposure.